Robert Houghwout Jackson papers - Jackson, Robert Houghwout, 1892-1954.
Correspondence, memoranda, family papers, legal file, subject file, speeches, writings, financial papers, transcripts of oral history interviews, biographical papers, photographs, and other papers documenting Jackson's legal career. Includes material from his private law practice in Jamestown, N.Y., relating to railroad, public utility, and textile mill cases there and a typhoid carrier case involving the Prudential Insurance Company of America. Jackson's years as assistant general counsel at the U.S. Bureau of Internal Revenue are documented by files relating to a case he prosecuted against Andrew W. Mellon, studies on the relationship of wealth to income taxes paid, and files relating to cases he tried while on detail to the U.S. Securities and Exchange Commission relating to the Public Utility Holdings Company Act of 1935.
Jackson's relationship with Franklin D. Roosevelt is reflected in his files (1936-1941) as assistant attorney general for the tax and antitrust divisions and as solicitor general and attorney general at the Justice Dept., particularly in cases concerning the implementation of New Deal programs and the constitutionality of the Social Security Act and in messages to Congress that Jackson helped Roosevelt draft. Other cases relate to the steel industry, automobile financing, oil prices, control of the aluminum industry by the Aluminum Company of America, and operations of the fuel, milk, motion picture, and utility industries. The approach of World War II is documented in cases relating to aircraft production, intelligence gathering, immigration and naturalization, investigation of subversive activities, selective service system, price stabilization and economic controls, taxation of excess profits by war material producers, embargo, and neutrality.
Jackson's Supreme Court files (1941-1954) include his opinions on cases involving Jehovah's Witnesses' civil liberties, treason, treatment of Japanese-Americans during World War II, Communist Party of the United States of America, taxing powers of states, government aid to private schools, and racial segregation in public school systems. Also included are Jackson's diary and working papers as head of the U.S. team for the prosecution at the Nuremberg war crime trials (1945-1946).
Correspondents include Sidney S. Alderman, Thurman Wesley Arnold, Wendell Berge, John L. Blair, Ernest Cawcroft, Homer S. Cummings, Gordon E. Dean, William O. Douglas, John E. Durkin, Charles Fairman, Felix Frankfurter, Whitney R. Harris, J. Edgar Hoover. Charles A. Horsky, Robert M. W. Kempner, Arthur Alden Kimball, Alfred A. Knopf, Frank Murphy, C. George Niebank, Stanley Forman Reed, Franklin D. Roosevelt, Charles B. Sears, Robert G. Storey, Herbert Bayard Swope, Telford Taylor, Philip J. Wickser, and John H. Wright. Letters of Jackson's son, William E. Jackson, and daughter, Mary Craighill, and of other family members are also included.
Microfilm of the Nuremberg War Crimes File, containers 95-106, available
Microfilm edition produced from originals in the Manuscript Division.
Library of Congress General Collection.
Library of Congress Geography and Map Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
U.S. Supreme Court justice, attorney general, and solicitor general, and lawyer.
Keywords: Alderman, Sidney S. -- 1892- -- Correspondence; Arnold, Thurman Wesley, -- 1891-1969 -- Correspondence; Berge, Wendell, -- 1903-1955 -- Correspondence; Blair, John L. -- 1888-1962 -- Correspondence; Cawcroft, Ernest -- Correspondence; Craighill, Mary -- Correspondence; Cummings, Homer S. -- 1870-1956 -- Correspondence; Dean, Gordon E., -- 1905-1958 -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Durkin, John E. -- Correspondence; Fairman, Charles, -- 1897- -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Harris, Whitney R. -- Correspondence; Hoover, J. Edgar -- 1895-1972 -- Correspondence; Horsky, Charles A. -- 1910-1997 -- Correspondence; Jackson, William E. -- Correspondence; Kempner, Robert M. W. -- 1899- -- Correspondence; Kimball, Arthur Alden, -- 1908- -- Correspondence; Knopf, Alfred A., -- 1892-1984 -- Correspondence; Mellon, Andrew W. -- 1855-1937.; Murphy, Frank, -- 1890-1949 -- Correspondence; Niebank, C. George -- 1925- -- Correspondence; Reed, Stanley Forman, -- 1884-1980 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Sears, Charles B. -- 1870-1950 -- Correspondence; Storey, Robert G. -- 1893-1981 -- Correspondence; Swope, Herbert Bayard, -- 1882-1958 -- Correspondence; Taylor, Telford -- Correspondence; Wickser, Philip J. -- 1887-1949 -- Correspondence; Wright, John H., -- 1867-1951 -- Correspondence; Aluminum Company of America; Communist Party of the United States of America; Prudential Insurance Company of America; United States. -- Bureau of Internal Revenue; United States. -- Department of Justice; United States. -- Department of Justice. -- Antitrust Division; United States. -- Department of Justice. -- Tax Division; United States. -- Securities and Exchange Commission; United States. -- Selective Service System; United States. -- Solicitor General; United States. -- Supreme Court; Aircraft industry -- Law and legislation -- United States; Aluminum industry and trade -- Law and legislation -- United States; Automobile industry and trade -- Finance -- United States; Constitutional law -- United States; Dairy laws -- United States; Embargo -- United States; Emigration and immigration -- Law and legislation -- United States; Fuel trade -- Law and legislation -- United States; Government aid to private schools -- United States; Income tax -- United States; Japanese Americans -- Evacuation and relocation, 1942-1945.; Jehovah's Witnesses -- Legal status, laws, etc. -- United States; Law -- United States; Motion picture industry -- Law and legislation -- United States; Naturalization -- United States; Neutrality -- United States; New Deal, 1933-1939.; Nuremberg War Crime Trials, Nuremberg, Germany, 1946-1949.; Petroleum products -- Prices -- United States